The ecosystem of irrigated paddy field - Nor Fadhilah Idris (2004., 2004)
Thsi project is carried out to produce a module for teaching and learning biology using multimedia technology. Multimedia is a proper teaching and learning systems and interactive in educational technology. This project is aimed to produce a biology teaching and learning modules based on computer. The title is "The Ecosystem of Irrigated Paddy Field" has been used for increasing the students comprehension for this module. Learning would be more effective and interesting if lessons are presented through a single computer compact disc (CD) that contains the simulations of the contents in the forms of audio visual, graphics, texts, animations and interactivity. As a conclusion, this module will help students in understanding about "The Ecosystem of Irrigated Paddy Field".
Project paper (B.S. cum. Ed. (Hons)) - Universiti Putra Malaysia, 2004.